Ethics, empathy, and empowerment: the role of ideological and political education in preparing medical students for adolescent female reproductive health care - Shouwei Guo; Juan Yan (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This study explores how ideological and political education contributes to equipping medical students with ethical sensitivity in providing adolescent reproductive healthcare. Using a quantitative cross-sectional design, the research surveyed Chinese medical students through a structured questionnaire assessing their exposure to such education, along with measures of ethical competence, empathy, empowerment orientation, and preparedness for care delivery. Data analysis encompassed descriptive statistics, correlation assessments, regression analysis, and mediation modeling. Results indicated a positive link between ideological and political education and enhanced preparedness for adolescent care. Ethical competence, empathy, and empowerment orientation served as mediators in this relationship, with empathy emerging as the most significant mediator. The findings highlight the importance of integrating values-based training into medical curricula to enhance students' readiness for ethical, gender-sensitive, and adolescent-centered care. This approach aligns strongly with the objectives of Sustainable Development Goals 3 and 5.